MVC software architecture pattern for web-application of system of monitoring of airport transport - B. P. Eliseev; A. V. Tarasenko; O. A. Gorbachev; D. Lyu (Научный вестник МГТУ ГА)
The article describes MVC and MVP patterns, ways of interaction and the role of each component of the pattern, the possibility of using services when developing an application. The diagrams of http-request-response pairs are presented when using services and without them. The main features of the AngularJS framework are described.